INTEGRATING DIGITAL ELEVATION MODELS AND STRATIGRAPHIC DATA FOR THE RECONSTRUCTION OF THE POST-LGM UNCONFORMITY IN THE BRENTA ALLUVIAL MEGAFAN (NORTH-EASTERN ITALY) - Mozzi, Paolo; Ferrarese, Francesco; Fontana, Alessandro (Alpine and Mediterranean Quaternary, 2013)
Stratigraphic cores and sections, geological maps and Digital Elevation Models (DEMs) were used for the threedimensional reconstruction of a portion of the regional unconformity, which separates the Last Glacial Maximum (LGM) sedimentary complex from the post-LGM one. The investigation focused on the Brenta megafan, a ca. 3000 km2 wide alluvial system that extends from the Alpine piedmont to the Venice Lagoon. During LGM the Brenta megafan experienced a major aggradation phase, which led the system to achieve its maximum extent. Fluvial downcutting started after 17.5 cal ka BP and led to the formation of incised valleys (IVs) in the plain, which reached depths up to 20-30 m. The interfluves between IVs experienced soil formation (Calcisols, Luvisols) until their burial by later deposits, or until present in the case of wide exposed stretches of LGM plain. A DEM of the present surface of the Brenta megafan and a geological map of the LGM deposits were created in a Geographic Information System (GIS). Seventeen cores and sections with information on the nature (erosive vs. hiatal with soil formation) and depth of burial of the post-LGM unconformity, as well as on the stratigraphy of the alluvial succession, were introduced in the GIS as stratigraphic control points (SCPs). Contours of the base of post-LGM sediments with 2-m interval were available in the Venice Lagoon and its mainland. Different interpolation and statistical methods were applied for modeling the unconformity in the pedogenized interfluves and in IVs. Contours were interpolated with Triangulated Irregular Network (TIN) technique. SCPs were interpolated with Inverse Distance Weight (IDW) algorithm with the function cos3 . Linear trend equations between the exposed top of the valley fill, i.e. the topographic surface in the DEM, and the unconformity elevation were calculated in different reaches of IVs. Data processing resulted in the production of a DEM of the post-LGM unconformity in the whole Brenta megafan with a cell size of 30x30 m. Morphometric analysis of the DEM enabled to evaluate the gradients of the unconformity in long and transverse profiles, as well as to calculate its overall extension (1491 km2 ), the areas characterized by buried soils (970 km2 ), and those which correspond to an erosive surface in IVs (521 km2 ). The difference between the DEM of the unconformity and the present topographic surface allowed for the first calculation of the volume of alluvial and coastal sediments which lie on top of the unconformity (10.4 km3 ), and of those which fill the IVs (4.3 km3 ). The unconformity was traced and modeled across a whole range of sedimentary environments, from braided gravel-bed channel belts (in the proximal sector) down to coastal barrier-and-lagoon systems. The method may be applied to neighboring megafans of the Venetian-Friulian and eastern Po Plain. Moreover, it can be extended offshore, in the shelf of Northern Adriatic Sea, to the tip of the deltaic systems, providing a valuable tool for basin-scale stratigraphic correlations and quantitative estimation of erosive processes and sedimentary storage.